UJI AKTIVITAS ANTIBAKTERI NANOPARTIKEL EKSTRAK ETANOL DAUN MATOA (Pometia pinnata J.R. Forst & G. Forst) TERHADAP BAKTERI Streptococcus mutans - Fahira, Nelsa; Rahayu, Yayuk Putri; Nasution, Haris Munandar; Nasution, M Pandapotan (Jurnal Riset Kefarmasian Indonesia, 2023)
Streptococcus mutans is one of the bacteria that plays an important role in the formation of dental caries. One of the plants known to have antibacterial compounds are matoa leaves (Pometia pinnata J.R. Forst & G. Forst) family Sapindaceae. The objective of this research was to determine the antibacterial activity of matoa leaves ethanolic extract nanoparticles is better than matoa leaves ethanolic extract against S. mutans bacteria. The research method was carried out experimentally. Free variables, namely the concentration of matoa leaf ethanol extract (KEDM 25% ; KEDM 50%; and KEDM 75%) and the concentration of nanoparticles of matoa leaf ethanol extract (KNDM 2.5%; KNDM 5%; and KNDM 7.5%). Bound variables are antibacterial activity of ethanol extract and nanoparticles of matoa leaf ethanol extract against S. mutans bacteria. The nanoparticle size of the extract was characterized using a Particle Size Analyzer (PSA). Test of antibacterial activity of ethanol extract and matoa leaf ethanol extract nanoparticles against S. mutans using the diffusion method to Kirby Bauer. The result of the extract nanoparticle size characterization was 324.97 nm. Zone of Inhibition (ZOI) values of antibacterial ethanol extract of matoa leaves against S. mutans were 12.00 mm (KEDM 25%), 12.50 mm (KEDM 50%), and 12.60 mm (KEDM 75%). The antibacterial ZOI values of matoa leaf ethanol extract nanoparticles against S. mutans were 8.00 mm (KNDM 2.5%), 9.06 mm (KNDM 5%), and 10.10 mm (KNDM 7.5%). The conclusion is that ethanol extract of matoa leaves can be used as extract nanoparticles, where the extract nanoparticle concentration of 7.5% already has the ability of antibacterial activity that is close to the concentration of 25% ethanol extract, so that it can be said that the extract nanoparticle preparation can reduce the dose of a drug even though it is in the resistant category compared to Amoxicillin 25 g with the susceptible category.